Synthesis, antimicrobial, anti-cancer and molecular docking of two novel hitherto unreported thiophenes. Issue 68 (5th July 2016) - Mabkhot, Yahia N.; Kheder, Nabila Abdelshafy; Barakat, Assem; Choudhary, Muhammad I.; Yousuf, Sammer; Frey, Wolfgang
Abstract : One pot synthesis of two novel hitherto unreported thiophenes was achieved by a facile and selective synthetic method. Abstract : One pot synthesis of two novel hitherto unreported thiophenes was achieved by a facile and selective synthetic method. The crystal structures of the synthesized compounds were determined using an X-ray single crystal technique. The synthesized thiophenes were evaluated for their anti-cancer and antimicrobial activities. Molecular docking studies of the synthesized compounds were performed by (MOE). The predicted results from the molecular docking studies were in complete agreement with the experimental data for antimicrobial evaluation.